The Effects of Rotation on the Evolution of the First Stars in the Universe - Murphy, Laura (Trinity College Dublin. School of Physics. Discipline of Physics, 2022)
Understanding the nature of the first stars is key to understanding the early Universe. With new facilities such as the James Webb Space Telescope we may soon have the first observations of the earliest stellar populations, but to understand these observations we require detailed theoretical models. In this thesis, we discuss the results of our work on the effects of rotation on the evolution of the first stars in the Universe. We have computed a new grid of stellar evolution models using the Geneva code with the aim to improve our understanding of the evolution of zero-metallicity stars, with particular interest in how rotation affects surface properties, interior structure, metal enrichment, and ionizing photon production. We have produced a range of models of initial masses from 1.7 to 120 solar masses, focusing on massive models of 9 to 120 solar masses, with and without rotation. This research has shown that rotation strongly impacts the evolution of the first stars, mainly through increased core size and stronger H-burning shells during core He burning. We have found that rotational mixing strongly affects metal enrichment, but may also hinder it depending on the initial mass and rotational velocity. Using this new grid of Pop III stars we have also predicted their ionizing photon production, and how that is impacted by rotation, convective overshooting, and the nature of the initial mass function. This work has advanced our understanding of the evolution of the first stars in the Universe, and will help us to interpret future detections of the first stars and their impact on their environments.
APPROVED
Keywords: Stellar Evolution; The First Stars; Astrophysics